Identification of The Relationship Between Behavioral Theory And Nurses' Intention in Documenting Nursing Care Using The Theory Of Planned Behavior in The Integrated Inpatient Care Unit Building A RSCM - Sartika, Dwi; Fauzan Azhmy, Muhammad; Syahyunan, Syahyunan (Sumber Belajar Sejahtera, 2025)
Nursing documentation is an important aspect of health services. This study aims to analyze the perception of nurses in RSCM regarding the importance of documentation, attitudes towards documentation, and factors that affect documentation practices. This study used a quantitative descriptive design with a cross-sectional approach. The research sample is all nurses at RSCM. Data collection was carried out through questionnaires. The results of the study show that most of the nurses in Building A RSCM strongly agree with the importance of nursing documentation and realize that good documentation can improve the quality of patient service. This is indicated by the r-table ≥ calculation with 15 items that have been declared valid. With KMO values of 0.772, 0.696, and 0.624 above 0.5 with a significance value (Sig.) of 0.000. In addition, there is a positive correlation between subjective norms and attitudes. The relationship between attitudes and subjective norms is quite strong. The majority of nurses also have a positive attitude towards documentation, such as being confident, consistent, and having good intentions. Factors that influence documentation practices include: a supportive work environment, availability of assistive devices, sufficient time, and support from colleagues. Integrated inpatient nurses in Building A of RSCM have a high awareness of the importance of nursing documentation. Positive attitudes and support from the work environment are important factors in improving the quality of documentation. However, there are still several obstacles that need to be considered, such as limited time and lack of priority in documentation.